Survey on the Sale of Megaphrynium Macrostachyum (Marantaceae) Leaves in Gbado-Lite City and Surroundings (Nord Ubangi Province, Democratic Republic of the Congo) - Koto-te-Nyiwa Ngbolua; Ngemale Gbiadiri Maurice; Masengo Ashande Colette; Ndolete Geregbia Jean-Pierre; Bongo Ngiala Gédéon; Ndanga Bikibo Apollinaire; Tshibangu Sha Tshibey Damien; Tshilanda Dinangay Dorothée (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
In Africa, the importance of NTFPs in the livelihood security is well recognized and these products represent vital sources of income for poor population. However, the sales chain of Marantaceae leaves is informal in Gbado-Lite and there is no information available on this sector for the promotion of the sale of NTFPs at the local level to reduce poverty and protect the environment as well as to conserve biodiversity. This survey shows that mostly female (55%) carries out the sale of Marantaceae leaves in Gbado-Lite. Among traders, 37.5% are illiterate, 32.5%, 20% and 10% have a secondary, primary and university education respectively. Regarding the marital status, 52.5% of respondents are divorced, 25% are widows and 22.5% are married. While 40% of respondents are unemployed, 30% are farmers while housewives and pupils account for 17.5% and 12.5% respectively. Our respondents know seven other non-woody forest products. These include: Mushrooms (27.5%), Caterpillars (22.5%), Marantaceae leaves (20%), honey (17.5%), snails and game (5% each) and vines (2.5%). Marantaceae leaves are first used for food packaging (47.5%), food preservation (35%), building material (10%). The forest accounts for 52% of the total harvesting habitat of Marantaceae leaves. It is followed by fallow (25%), fields (15%) savannah (8%) respectively. This sale allows the schooling for children (27.5%); health care (20%); food purchase (17%); beverage purchase (12.5%). The majority of respondents believe that these leaves are not well managed after use and therefore pollute the environment because of the lack of a waste collection structure. Yet, they are biodegradable and should be used to make compost for crops in Gbado-Lite.